Advancements in Human-Computer Interaction: A Review of Recent Research - Hasyim, Hasyim; Bakri, Muhammad (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study explores advancements in Human-Computer Interaction (HCI), focusing on how AI and VR technologies can enhance long-term emotional engagement, cultural inclusivity, and accessibility. The research seeks to fill gaps in understanding HCI's emotional and social dimensions by addressing how these technologies affect users' cognitive and emotional well-being over time. Research Design and Methodology: The study uses a qualitative systematic literature review to analyze critical academic and industry research on AI, VR, and HCI. Through a thematic analysis, it identifies trends and challenges in designing more inclusive, emotionally responsive, and culturally adaptive systems. Findings and Discussion: The study reveals that while AI and VR technologies improve user engagement, there are significant gaps in cultural inclusivity and emotional responsiveness, especially for users with disabilities. It also proposes theoretical models integrating emotional and cultural factors into HCI design, enabling adaptive and personalized user experiences. Implications: This research shows the need for HCI technologies to prioritize emotional engagement and inclusivity. Practically, these findings can guide the development of more adaptive AI and VR systems that cater to diverse user needs, offering better accessibility and user satisfaction. Future research should explore empirical applications of these theoretical models in specific industries, such as healthcare and education.